Role of Dsg1- and Dsg3-Mediated Signaling in Pemphigus Autoantibody-Induced Loss of Keratinocyte Cohesion - Walter, Elias; Vielmuth, Franziska; Wanuske, Marie-Therès; Seifert, Matthias; Pollmann, Robert; Eming, Rüdiger; Waschke, Jens (Frontiers in Immunology, 2019)
Pemphigus is an autoimmune dermatosis in which mucocutaneous blisters are induced primarily by autoantibodies against Desmoglein (Dsg) 1 and 3. Pemphigus vulgaris (PV) usually is associated with autoantibodies against Dsg3 whereas pemphigus foliaceus (PF) patients present autoantibodies against Dsg1. Several signaling pathways were proposed to cause loss of keratinocyte adhesion. However, relevance of different signaling pathways and role of Dsg1 and 3 to trigger signaling are not fully understood. Here, we show that Ca2+ chelation reduced PV-IgG- and PF-IgG-mediated loss of HaCaT keratinocyte cohesion whereas EGFR inhibition did not inhibit effects of PF-IgG. PV-IgG activated EGFR in a Src-dependent manner whereas both PV-IgG and PF-IgG caused Ca2+ influx independent of EGFR. ERK activation was Src-dependent in response to PV-IgG but not PF-IgG. To delineate the roles of Dsg isoforms to trigger signaling pathways, Dsg3- and Dsg2-deficient HaCaT keratinocyte cell lines were generated using CRISPR/Cas9. Dsg3- but not Dsg2-deficient cells were protected against PV-IgG-induced loss of cell adhesion. Ca2+ influx and ERK activation in response to PF-IgG were preserved in both cell lines.